Evaluation of Lemon Peel Extract as Hepatoprotective Agent against Paracetamol-Induced Liver Toxicity: Insights from Biochemical Studies - Charmkar, Radhe Prasad; Dubey, Nazneen; Ganeshpurkar, Aditya (Free Radicals and Antioxidants)
Background: The liver serves as a vital organ in metabolic processes and detoxification, making it susceptible to damage induced by xenobiotics such as drugs. Paracetamol overdose is a common cause of hepatotoxicity. Traditional medicine has long explored botanical sources for hepatoprotective agents, highlighting the potential of natural compounds in mitigating liver damage. Lemon peel, rich in flavonoids with antioxidant properties, presents a promising candidate for hepatoprotection. Materials and Methods: This study aimed to investigate the hepatoprotective effects of lemon peel extract on paracetamol-induced liver toxicity in rats. The extract was prepared through standardized extraction procedures and its dose was selected based on previous studies. Wistar rats were divided into five groups and subjected to various treatments, including paracetamol overdose with or without lemon peel extract supplementation. Biochemical parameters indicative of liver function, such as serum levels of AST, ALT, ALP and bilirubin, were measured following treatment protocols. Results: Administration of paracetamol alone induced significant elevation in serum levels of AST, ALT, ALP and bilirubin, reflecting hepatocellular damage. However, co-administration of lemon peel extract with paracetamol resulted in reduced levels of these biochemical markers compared to the paracetamol-only group. The decrease in enzyme levels suggests potential hepatoprotective effects of lemon peel extract. Conclusion: Lemon peel extract demonstrated hepatoprotective effects against paracetamol-induced liver toxicity in rats, as evidenced by the attenuation of biochemical markers indicative of liver damage. These findings highlight the therapeutic potential of lemon peel extract as a natural remedy for protecting liver health and mitigating the adverse effects of hepatotoxic agents.
Keywords: Hepatoprotective; Lemon Peel Extract; Paracetamol-Induced Liver Toxicity; Biochemical Studies